2011
DOI: 10.2355/isijinternational.51.1179
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Hydrocalumite-like Adsorbent from Blast Furnace Slag using Alkali Fusion

Abstract: Blast furnace (BF) slag, one of the byproducts of iron-and steel-making plants, was converted into a hydrocalumite-like compound using the alkali fusion method. The slag was transformed into the precursor with reactive phases via alkali fusion, after which the precursor was added to distilled water and stirred at room temperature to synthesize the product including a hydrocalumite-like compound. The effects of the mixed ratio of NaOH to the slag (NaOH/slag ratio), fusion temperature, ratio of precursor mass to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 10 publications
(11 reference statements)
0
10
0
Order By: Relevance
“…The synthesis of CaAl-LDH phases could be affected by various factors such as the species variation of main components, thermodynamic characteristics of starting materials, and reaction routes [ 19 , 27 , 28 , 29 ]. The various factors are determined by the type of synthesis method, temperature, anion, and pH value and so on.…”
Section: Calcium Aluminate-layered Double Hydroxide Phasesmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis of CaAl-LDH phases could be affected by various factors such as the species variation of main components, thermodynamic characteristics of starting materials, and reaction routes [ 19 , 27 , 28 , 29 ]. The various factors are determined by the type of synthesis method, temperature, anion, and pH value and so on.…”
Section: Calcium Aluminate-layered Double Hydroxide Phasesmentioning
confidence: 99%
“…In this context, the adsorption process with various absorbents has been adopted, owing to the simple operation and cost-effectiveness [ 16 ]. Iron oxides and hydroxides, titanium, and some composites with iron and titanium have been often used as an adsorbent [ 16 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…For hydrocalumite, Ca 2+ and Al 3+ , fixed in a molar ratio of two, are seven and sixfold coordinated, respectively, being the seventh ligand of the Ca-polyhedron a water molecule from the interlayer [5]. Hydrocalumites have been extensively used in the immobilization of toxic cations [4][5][6][7][8][9][10][11], the optimization of concrete properties [2,3,[12][13][14], and, in less extent, for catalysis due to their basic properties [15]. The structure of hydrocalumites collapses at temperatures between 400 and 600°C due to the dehydroxylation of their octahedral layers, giving rise to the formation of an amorphous, basic Ca-Al mixed oxide, Ca(Al)O x , which may be also used as catalyst for organic reactions such as the Meerwein-PonndorfVerley reaction [16], the isomerization of 1-butene [17] or the transesterification of castor bean oil and methanol [18].…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis procedure was given in a previous paper [21] . A 2.5 g sample of BFS was mixed with 4.0 g of NaOH powder, and ground to obtain a homogeneous mixture.…”
Section: Synthesismentioning
confidence: 99%
“…In our previous study, we converted BFS into a hydroxidebased adsorbent, containing hydrocalumite and calcite, using alkali fusion, and confirmed that the adsorbent has high affinity for phosphate from aqueous solution [21] . While this adsorbent is expected to be useful to remove phosphate from aqueous solution, more information is required on its properties before it can be widely applied.…”
Section: Introductionmentioning
confidence: 99%